Creativity, Psychoanalysis and Eugene O’Neill’s Creative Process - Karim, Asim; Butt, Nasim Riaz (k@ta: A Biannual Publication on the Study of Language and Literature, 2012)
O’Neill is undisputedly one of the most autobiographical artists in modern literature. His creativity consistently moves around subjective exploration and autobiographical representation in his art. Therefore drama for him involves primarily dramatization of self and close relations such as mother, father and brother, and this association between life and art goes back to early amateur plays. This factor has exposed the artist to discreet psychoanalytic explorations and analysis. Clearly a depressive and predominantly oedipal pattern emerges in his writings that could be traced in the whole range of his plays. However, preoccupation with the self and pervasive obsession to dramatize peculiar relationships and psychic conditions create its own archeology of limitations in his art that have remained unaddressed so far. The study debates on creativity, psychoanalytic traditions of creativity, O’Neill’s creative process and highlights some of the limitations that pertain to representative and intellectual aspects of his art